2021
DOI: 10.1515/jbcpp-2020-0323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Onosma dichroanthum Boiss. root extract on AGS human gastric cancer cell-line

Abstract: One of the cancer-related deaths is gastric cancer in this area. Onosma dichroanthum Boiss. roots have been used as an antiseptic and anti-inflammatory for wound healing treatment. The aim of this study was to assess the in vitro cytotoxic and anticancer effects of O. dichroanthum Boiss. roots from the Golestan province of Iran. After identification of the taxonomical effect of O. dichroanthum Boiss., different concentrations of the hydroalcoholic root extract were used. Three different time periods (24, 48, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The genus Onosma, known to be widespread worldwide, has a history of medicinal uses against different diseases in the folk medicine system of several civilizations. In this review, the authors rediscover the genus Onosma by detailing the important isolated and identified chemical compounds and extracts, including naphthoquinone (33), flavonoids (30), hydrocarbon (23), phenolic (22), ester (17), alkaloids (20), terpenoids (10), carboxylic acid (11), fatty acids (9), aromatics (12), and liganin (5). The Onosma phytoconstituents that are considered as potential leads amenable for drug development were reported as rosmarinic acid, apigenin, ferulic acid, protocatechuic acid, chlorogenic acid, caffeic acid, p-coumaric acid, vanillic acid.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The genus Onosma, known to be widespread worldwide, has a history of medicinal uses against different diseases in the folk medicine system of several civilizations. In this review, the authors rediscover the genus Onosma by detailing the important isolated and identified chemical compounds and extracts, including naphthoquinone (33), flavonoids (30), hydrocarbon (23), phenolic (22), ester (17), alkaloids (20), terpenoids (10), carboxylic acid (11), fatty acids (9), aromatics (12), and liganin (5). The Onosma phytoconstituents that are considered as potential leads amenable for drug development were reported as rosmarinic acid, apigenin, ferulic acid, protocatechuic acid, chlorogenic acid, caffeic acid, p-coumaric acid, vanillic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The current systematic review of the phytochemical contents of Onosma species presents major identified organic classes such as naphthoquinone (33), flavonoids (30), hydrocarbon (23), phenolic (22), ester (17), alkaloids (20), terpenoids (10), carboxylic acid (11), fatty acids (9), aromatics (12), and liganin (5) compounds as shown in Figure 4. In addition, miscellaneous chemicals such as 24,25-Dihydroxycholecalciferol, 5-hydroxymethyl-furoic acid, and uplandicine also enrich the diversity of the phytochemistry in Onosma plants.…”
Section: Chemical Profile Of Onosma Speciesmentioning
confidence: 99%
See 3 more Smart Citations